Negative Words and Their Classifications in English Language Sentence Structure - Muradova Sevara Zoir Kizi (Periodica Journal, 2023)
This paper is devoted to the theoretical significance of the work deceptions in the further modification of presently available demonstrations about details and origin of negative words, their use in sentence structure, and a lot of scholars’ works about negative word forms are discussed
Keywords: words; regular meaning; structure